Application of TOPSIS Method for Analysis of Sustainable Development in European Union Countries - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2016)
The main purpose of the research is to examine the progress achieved by European countries in the field of implementing the concept of sustainable development and to point the group of countries that can be considered as leaders in that sphere. The research is based on the Eurostat data and it is conducted at macroeconomic level in the years 2004-2013. The sustainable development concept should be considered as a multidimensional phenomenon. Thus, Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was used in the research. TOPSIS method allows to evaluate the objects in terms of multidimensional economic phenomena based on the set of detailed economic attributes (variables). The dynamic synthetic index describing the relative level of sustainable development of the countries was created, which enabled to propose a rating of the countries and group them into homogenous subsets. The grouping was conducted with application of natural breaks method. The comparison of the ratings in the period 2004-2013 shows that most of the new member states of European Union have made a significant progress in implementing the concept of sustainable development. The research enabled to point the countries that are the leaders in the field.
Keywords: C38; Q01; 330; multiple-criteria decision analysis (MCDA); TOPSIS method; sustainable development; European Union